Rethinking Multiculturalism in a Homogeneous Society: A Qualitative Inquiry into Muslim Integration in South Korea - Mohd Ghazi, Ahmad Faris Naqiyuddin; Mohamad Jamil, Asyiqah; Mohd Ghazi, Ahmad Fauzan; Karaman, Mert Sabri (Advances in Humanities and Contemporary Studies, 2025)
South Korea’s transition from a historically homogeneous society to an increasingly diverse nation has generated new debates over the meaning and limits of multiculturalism. While state initiatives such as the Support for Multicultural Families Act signify formal recognition of diversity, they also expose the selective and assimilationist tendencies embedded within South Korea’s policy framework. This study employs a qualitative document analysis of policy texts, academic scholarship, and media discourse to critically examine how multiculturalism is constructed, represented, and experienced particularly through the lens of Muslim minority integration. Findings reveal that South Korea’s multiculturalism remains state-managed and conditional, privileging “acceptable” forms of diversity such as marriage migrants and multicultural families while marginalizing others, including Muslim laborers, refugees, and converts. Media representations further reinforce this exclusion by securitizing Muslim identity and framing religious difference as a threat to national cohesion. Educational curricula, meanwhile, reproduce cultural homogeneity by avoiding critical engagement with religion and pluralism. Despite these constraints, Muslim communities demonstrate agency through faith-based organizations, social networks, and everyday negotiations of belonging. The study argues that South Korea’s current multicultural paradigm sustains inclusion without equality and recognition without acceptance. To achieve genuine pluralism, the nation must move beyond symbolic diversity toward intercultural citizenship grounded in equality, dialogue, and mutual respect.